A Inserção da astronomia na grade curricular do ensino médio do Estado de São Paulo - Santos, Clayton Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
We performed in this study an analysis of Curriculum Astronomy contents the public schools of São Paulo from the available educational materials to teachers and students by the state board of education. We analyzed the conditions that teachers carry out the activities suggested to the teaching-learning situations, considering factors such as time available for classes, available material and the general technical condition to perform the activities suggested by the material. Thereafter, we conducted a search with teachers from public of São Paulo, than three cities in the Vale do Paraíba, in order to trace a general framework of the perception of these teachers about the introduction of Astronomy in Physical during the implementation of the new curriculum

Realizamos neste trabalho uma análise dos conteúdos de Astronomia do Currículo da rede pública do Estado de São Paulo a partir dos materiais educacionais disponibilizados aos professores e alunos pela Secretaria Estadual de Educação. Analisamos as condições em que os professores executam as atividades sugeridas para as situações de ensino-aprendizado, considerando fatores como tempo disponível para aulas, material indicado e condições técnicas gerais para a realização das atividades sugeridas pelo material. Posteriormente, realizamos uma pesquisa com professores da rede pública de São Paulo, de três cidades do Vale do Paraíba, com intuito de traçar um panorama geral da percepção desses professores sobre a introdução da Astronomia na disciplina de Física durante o período de implementação do novo Currículo
Keywords: Astronomia - Estudo e ensino; Ensino médio; Curriculos - Planejamento; Escolas públicas; Astronomy Study and teaching